Diagnosis, testing, treatment, and outcomes among patients with advanced non‐small cell lung cancer in the United States - Mo Yang; Joanna P. MacEwan; Sai Sriteja Boppudi; Monica R. McClain; Richard M. O'Hara Jr; Paul K. Paik (Cancer Medicine, 2023)
Abstract Introduction Characteristics of patients in clinical trials may differ from those of real‐world patients. Our objective was to describe biomarker testing and outcomes among patients with advanced non‐small cell lung cancer (aNSCLC) in a real‐world setting. Methods This retrospective cohort study included patients ≥18 years old, diagnosed with stage IIIB/C or IV NSCLC, and in the TEMPUS oncology dataset from January 1, 2012, to December 31, 2020. Patient characteristics associated with biomarker testing were evaluated in patients with positive biomarkers using univariate logistic regression models. Cox proportional hazard models were used to estimate median survival. Results Of 9540 patients included, 41.7% had biomarker testing, and 2158 had a positive biomarker result. Men (vs women; odds ratio [OR], 0.82; 95% CI: 0.74–0.91), Black patients (vs White; OR, 0.83; 95% CI: 0.72–0.97), patients with squamous (OR, 0.22; 95% CI: 0.19–0.25) or unknown histology (OR, 0.53; 95% CI: 0.45–0.61) (vs non‐squamous histology), and patients with an Eastern Cooperative Oncology Group performance status (ECOG PS) of 2+ (OR, 0.69; 95% CI: 0.57–0.84) or missing (OR, 0.56; 95% CI: 0.48–0.66) (vs ECOG PS of 0) were less likely to undergo biomarker testing. Patients with positive biomarkers who received NCCN‐recommended treatment options (55.7%) had significantly longer median overall survival (OS) (hazard ratio [HR], 0.84; 95% CI: 0.75–0.95) and real‐world progression‐free survival (rwPFS) (HR, 0.68; 95% CI: 0.62–0.75). Conclusion More than 50% of patients were untested for biomarkers. Patients who were less likely to be tested included men, Black patients, current smokers, patients with squamous aNSCLC, and patients with an ECOG PS of 2+. Patients with positive biomarkers who received NCCN‐recommended treatment options had significantly longer OS and PFS.